DFT study on the alternative NH3 formation path and its functional group effect. (15th February 2018) - Zhang, Hai; Liu, Jiaxun; Liu, Jianguo; Luo, Lei; Jiang, Xiumin
Highlights: The NH3 formation mechanism are proposed by DFT modelling. Intermediates and some important transition states are characterized. The reaction energy and activation energy are evaluated. The functional group influence on the energy property is investigated. Abstract: This study attempts to better understand through DFT calculations the NH3 formation mechanism associated with the reaction energy and barrier height. The formation of NH3 can be completed by (1) heterogeneous nitrogen migration; (2) NH2 desorption; and (3) homogeneous H-abstraction. Several transition structures have been characterized and we can conclude from energy analysis of these species that the heterogeneous nitrogen migration is the rate determining step and the formation of NH3 is largely dependent on the char-N stability. The NH3 formation is affected not only by the availability of H radicals but also by the vicinity of functional groups. The functional group effect is then investigated and further analyzed by the transferring of valence electrons and NBO charges. The results seem to be clear that NH3 formation is group-dependent. For example, the OH group acting as an electron donor will activate the carbonaceous surface and decrease the barrier height and the endothermicity, while the electron-withdrawing NO2 group plays an opposite role. Our work gives the molecular-level understanding for the previous experimental finding that oxygen-containing functional groups are important for the NH3 formation.